Ekstrak Jahe (Zingiber Officinale Roscoe) Berpengaruh Terhadap Kepadatan Serabut Kolagen Luka Insisi - Suharto, Idola Perdana Sulistyoning; Etika, Arif Nurma (Care : Jurnal Ilmiah Ilmu Kesehatan, 2019)
Wound is a condition of damage to the anatomical structure of the skin causing skin disorders (Moenadjat, 2003). There are three phases in the wound healing process. These phases are the inflammatory, proliferative and maturation phases. Ginger has several active substances. The several active substances contained in ginger, namely triterpenoids, flavonoids and saponins. Flavonoid compounds has a role in activating macrophages. Saponins are able to activate TGF-β signals. The aim of this research was to analyze the effect of ginger extract to the density of collagen fibers in rats (Rattus norvegicus) with incision wounds. This study was an experimental research laboratory, with a post-test only control group design. Rats were divided into two major groups: control group (KK) who were given only the solvent CMC 1% and the treatment group (KP) were given orally at a dose of ginger extract 1 g / kg. Rat tissue will be observed on days 1, 5 and 10. Data were analyzed by one-way ANOVA test with p value 0.125. The conclusion of this study is there was no significant difference in collagen density between the control and treatment groups. Based on the results of this study it can be concluded that the giving of ginger (Zingiber officinale roscoe) can increase the density of incisional collagen even though it has insignificant differences